Kaesang's Coat-Tail Effect: Influence and Implications for PSI's Political Branding in the 2024 Election - Siregar, Kristian Hamonangan; Rahmawati, Restu (UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. In the Indonesian political system, the coat-tail effect phenomenon is often utilized by political parties to increase electability through popular public figures. The coat-tail effect refers to a situation where the popularity of a figure can have a positive impact on vote support for other parties or candidates affiliated with them. One example of the implementation of this strategy is the appointment of Kaesang Pangarep, President Joko Widodo's youngest son, as Chairman of the Indonesian Solidarity Party (PSI) ahead of the 2024 elections. With his popularity as a young figure and his closeness to the president, Kaesang was expected to boost PSI's votes to reach the 4% parliamentary threshold. This study aims to analyze the influence and implications of Kaesang Pangarep's Coat-tail effect in increasing the votes of the Indonesian Solidarity Party (PSI) in the 2024 Election using a political branding approach. The research method used is qualitative and non-participant observation. The results showed that despite Kaesang's high popularity as a public figure, his involvement did not succeed in pushing PSI over the 4% parliamentary threshold, with votes only reaching 2.8%. Some of the main factors that led to this failure include the weak institutionalization of PSI's ideology, delays in campaign strategy, and the negative sentiment towards dynastic politics attached to Kaesang's figure. The research also found that Kaesang's presence managed to increase public attention, especially among young voters. This finding confirms that the popularity of public figures must be balanced with a structured political branding strategy and strong party ideological values to create a significant electoral impact. Keywords: Coat-tail effect, Political branding, Indonesian Solidarity Party (PSI), Election 2024. Abstrak. Dalam sistem politik Indonesia, fenomena coat-tail effect sering dimanfaatkan oleh partai-partai politik untuk meningkatkan elektabilitas melalui tokoh-tokoh publik yang populer. Coat-tail effect mengacu pada situasi di mana popularitas seorang figur dapat membawa dampak positif terhadap dukungan suara bagi partai atau kandidat lain yang berafiliasi dengannya. Salah satu contoh penerapan strategi ini adalah pengangkatan Kaesang Pangarep, putra bungsu Presiden Joko Widodo, sebagai Ketua Umum Partai Solidaritas Indonesia (PSI) menjelang Pemilu 2024. Dengan popularitasnya sebagai figur muda dan kedekatannya dengan presiden, Kaesang diharapkan dapat mendongkrak suara PSI agar mencapai ambang batas parlemen sebesar 4%. Penelitian ini bertujuan untuk menganalisis pengaruh dan implikasi Coat-tail effect Kaesang Pangarep dalam meningkatkan suara Partai Solidaritas Indonesia (PSI) pada Pemilu 2024 dengan menggunakan pendekatan political branding. Metode penelitian yang digunakan adalah kualitatif dan observasi non-partisipan. Hasil penelitian menunjukkan bahwa meskipun Kaesang memiliki popularitas tinggi sebagai figur publik, keterlibatannya tidak berhasil mendorong PSI melewati ambang batas parlemen sebesar 4%, dengan perolehan suara hanya mencapai 2,8%. Beberapa faktor utama yang menyebabkan kegagalan ini meliputi lemahnya pelembagaan ideologi PSI, keterlambatan dalam strategi kampanye, dan sentimen negatif terhadap politik dinasti yang melekat pada sosok Kaesang. penelitian juga menemukan bahwa kehadiran Kaesang berhasil meningkatkan perhatian publik, terutama dari kalangan pemilih muda. Temuan ini menegaskan bahwa popularitas figur publik harus diimbangi dengan strategi branding politik yang terstruktur dan nilai ideologis partai yang kuat untuk menciptakan dampak elektoral yang signifikan. Kata Kunci: Coat-tail effect, Political Branding, Partai Solidaritas Indonesia (PSI), Pemilu 2024.